Identity and the emergence of South African advertising esperanto - Stephanie Cawood; Jaqueline du Toit (Communicare)
There is no formal regulation of language use in the advertising industry to correspond to the declared commitment to multilingualism in the South African Constitution. A trend in television advertising, where language diversity, translation, and/or reconceptualisation are circumvented by conceptualising a visual message devoid of voice-over, is the subject of this article. The purpose is to consider the extent to which this practice undermines or contributes to the perception of a homogeneous marketplace and advertising language/esperanto. Visual texts provide a rich alternative, but carry the inherent burden of the intermingling of text and subtext not conveyed by means of language. The suggestion is that this global homogenising trend for target audiences, developed in advertising copy, has since transcended advertising parameters to include all kinds of copy. Language as marker of culture is being written out of the definition of cultural specificity as one of the primary means of identifying target audience. By merging their expertise in critical linguistics, document design and cultural and media studies, the authors offer qualitative and quantitative data in support of their argument.